Enantioselective synthesis of chiral 2,3-cis-disubstituted piperidines and C1-substituted tetrahydroisoquinolines by asymmetric Cu-catalyzed cyclizative aminoboration - Dazhuang Zhang; He Yang; Qinghai Zhou; Wenjun Tang (Nature Communications)
Abstract Chiral N-heterocycles such as piperidines and tetrahydroisoquinolines are privileged structural motifs in drug discovery and pharmaceutical industry. The development of efficient and practical asymmetric synthetic methods towards pharmaceutically important chiral N-heterocycles constitutes an important subject in synthetic chemistry. Asymmetric synthesis of 2,3-cis-disubstituted piperidines bearing two consecutive chiral centers is particularly challenging in terms of both diastereoselective and enantioselective control. In this work, a regiospecific and enantioselective cyclizative aminoboration is designed to tackle this problem by employing Cu/(S, S)-Ph-BPE as the chiral catalyst, leading to a series of 2,3-cis-disubstituted piperidines as well as C1-substituted tetrahydroisoquinolines in moderate to good yields and excellent enantioselectivities. The asymmetric six-membered ring-closing aminoboration features a broad substrate scope, mild reaction conditions, and excellent functional group compatibility. DFT calculation reveals the importance of noncovalent interactions between substrate and Cu catalyst in controlling the enantioselectivity. The synthetic utility and practicality of this cyclization protocol have been exemplified by the synthesis of the key chiral intermediates of avacopan and L-733,060.